FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN INFRASTRUKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - WIBOWO, SATRIYO; MILLAH, ADILA AINUN (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
This study aims to test and determine the effect of profitability, liquidity, company size, asset structure, business risk, and sales growth on capital structure, where the results of this study are then compared with the results of previous studies. The data used in this study were obtained from the financial statements of infrastructure sector companies listed on the Indonesia Stock Exchange for the period 2017-2023. With purposive sampling technique, there were 40 companies that met the criteria and were analyzed using panel data regression techniques. The results of this study indicate that liquidity and company size variables affect capital structure while profitability, asset structure, business risk, and sales growth variables do not affect capital structure.